Why do 'fast track' patients stay more than four hours in the emergency department? An investigation of factors that predict length of stay. (23rd March 2018) - Gill, Stephen D; Lane, Stephen E; Sheridan, Michael; Ellis, Elizabeth; Smith, Darren; Stella, Julian
Abstract: Objective: Low‐acuity 'fast track' patients represent a large portion of Australian EDs' workload and must be managed efficiently to meet the National Emergency Access Target. The current study determined the relative importance and estimated marginal effects of patient and system‐related variables in predicting ED fast track patients who stayed longer than 4 h in the ED. Methods: Data for ED presentations between 1 July 2014 and 30 June 2015 were collected from a large regional Australian public hospital. Only 'fast track' patients were included in the analysis. A gradient boosting machine was used to predict which patients would have an ED length of stay greater or less than 4 h. The performance of the final model was tested using a validation data set that was withheld from the initial analysis. A total of 27 variables were analysed. Results: The model's performance was very good (area under receiver operating characteristic curve 0.89, where 1.0 is perfect prediction). The five most important variables for predicting length of stay were time‐dependent and system‐related (not patient‐related); these were the amount of time taken from when the patient arrived at the ED to: (i) order imaging; (ii) order pathology; (iii) request admission to hospital; (iv) allocate a clinician to care for the patient; and (v) handover a patient between ED clinicians. Conclusions: We identified the most important variables for predicting length of stay greater than 4 h for fast track patients in our ED. Identifying factors that influence length of stay is a necessary step towards understanding ED patient flow and identifying improvement opportunities.